Effect of base metal oxygen content and oxygen activity on mechanical properties of EN-GJL- GG - 26 Cu-Cr grey cast-iron heavy-duty crank cases - Senyolo, Morokolo (Department of Mechanical Engineering, 2026)
Grey cast iron is a type of cast iron named for its grey appearance due to the presence of graphite flakes in the material. It is widely used in engine components, because of its wide range of mechanical and physical properties, which include strong heat conductivity, vibration damping capabilities, and superior machinability. One of the key development trends for grey cast-iron applications is the need for increased tensile strength, which will allow higher peak engine pressure, that leads to more efficient combustion and lower emissions. This research investigates how the oxygen content and oxygen activity of the liquid EN-GJL-GG - 26 Cu-Cr Grey Cast Iron metal are affected by holding the metal for a duration of 0 to 24 hours in a closed furnace/inert atmosphere, and how the addition of reactive iron oxide from 0 to 0.2wt% affects the oxygen content and activity at the different holding duration, and what will be its impact on the graphite morphology and the resulting mechanical properties. This report has documented the rigorous experimental approach and parameter measurement protocols and has presented the results of all the relevant measurements which were collected with minimal experimental error. However, for the most part, the measurements have indicated a minimal effect of the process variables listed above on the behaviour of the grey iron. The spread in data measurement, as indicated on the graph plots, and the overlapping values means that in many instances definitive trends could not be recognised. However, some noteworthy findings are indicated below: Oxygen content and activity of the melt decrease with increasing holding time, with no clear relation between wt% FeO addition and resulting oxygen content and activity. Oxygen content and activity are directly proportional, the volume fraction of Type E graphite in microstructure increases with increasing wt%FeO addition, oxygen content and activity. The tensile strength and hardness are insignificantly affected by changes in wt%FeO additions, oxygen content and activity.